Architecture as measure - Turan, Neyran (2019)
"In light of the current political crisis around climate change, what can architecture possibly contribute towards a new planetary imaginary of our contemporary environment, beyond environmentalism and technological determinism? Architecture as measure is an elaboration on the disciplinary and cultural potentials of such a provocation. It positions climate change as a cultural and political idea that requires a renewed architectural environmental imagination"--Back cover
Includes bibliographical references.
Keywords: Architecture and climate; Architecture -- Philosophy; Architecture and climate; Architecture -- Philosophy